2018
DOI: 10.5114/ceh.2018.75959
|View full text |Cite
|
Sign up to set email alerts
|

SX-Ella Danis stent in massive upper gastrointestinal bleeding in cirrhosis – a case series

Abstract: We report our experience of three cases of decompensated cirrhosis with massive upper gastrointestinal bleeding, which required insertion of an SX-Ella Danis stent for hemostasis. The procedure is safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Importantly, this data set includes a substantial number of cases early in the experience of many users as data was collected from the point of introduction of this new device at each center. This is in keeping with the extremely high technical success rates (90 %-100 %) described in the limited existing literature 16 17 18 20 21 24 25 26 . Interestingly, only eight of 32 SEMS (25 %) were placed by interventional endoscopists, suggesting that training in advanced endoscopic techniques is not necessarily required for successful deployment of the SEMS.…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, this data set includes a substantial number of cases early in the experience of many users as data was collected from the point of introduction of this new device at each center. This is in keeping with the extremely high technical success rates (90 %-100 %) described in the limited existing literature 16 17 18 20 21 24 25 26 . Interestingly, only eight of 32 SEMS (25 %) were placed by interventional endoscopists, suggesting that training in advanced endoscopic techniques is not necessarily required for successful deployment of the SEMS.…”
Section: Discussionsupporting
confidence: 82%
“…Self-expanding covered stents work in a similar fashion as balloon tamponade by applying pressure to the mucosa and compressing vessels. Jain et al reported that esophageal stents may also be used to control bleeding secondary to post-banding esophageal ulcers [18]. However, safe placement of a stent requires additional training and experienced staff that may not be available in emergencies, especially if fluoroscopy is necessary when through-the-scope stents are not offered.…”
Section: Discussionmentioning
confidence: 99%
“…Fully covered SEMS (Ella Danis) is increasingly being used with the same indication. 56 Hemostatic powders have been used for post-EVL ulcers, and currently are used as a bridging therapy until definitive endoscopy is possible. 57 The only validated option when hemospray is not available, is injection of cyanoacrylate beneath the ulcer base in conjunction with pharmacotherapy.…”
Section: Variceal Bleed Esophageal Variceal Bleedmentioning
confidence: 99%